Permeability Properties of Crushed Stone Aggregates in Bedding Course of Urban Permeable Roads: An Experimental Study - Rongrong Mao; Haiyan Yang (Advances in Civil Engineering)
Crushed stone is the most common material for use in the aggregate of bedding course. The aggregate for the bedding course of permeable roads needs to not only meet the requirements of basic mechanical properties but also ensure permeability and structural stability. This work analyzed permeability under extreme rainfall conditions and the particle mass loss during permeation and then investigated the stability of crushed stone aggregate and examined the optimal gradation and compaction levels of the crushed stone aggregate in engineering applications. It shows that (1) the permeation process included two phases, and the change of permeation velocity mainly occurred in the first phase. The permeation velocity of samples with different gradations at different compaction levels showed a stepwise change in its order of magnitude. (2) The change in permeability coincided with the change in flowrate, most probably because the sudden change of the flow altered the permeability of the sample. Factors such as gradation, compaction, and the randomness of particles arrangement in the crushed stone during sample charging all affected the permeability of the sample. (3) During the permeation process, the mass loss decreased with rising gradation. The gradation and compaction had strong influence on particle mass loss. Therefore, ensuring the structural stability of permeable road necessitates careful selection of the gradation and compaction for the crushed stone aggregate. It is recommended to use the crushed stone sample with a gradation of n = 0.7 and a compaction level of no greater than 20 mm for the aggregate of the bedding course.